2018
DOI: 10.3126/jpan.v6i2.21760
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression as Co-morbidities in Patients with Primary Headache

Abstract: Introduction: Headache is a common neurological disorder and psychiatric comorbidity is very common in primary headache in which anxiety and depression is more common. Data of patients presenting with primary headache and psychiatric comorbidity is scanty in Nepal. The aim of the study was to study the socio-demographic and clinical profile of patients with primary headache, and to study the frequency and pattern of anxiety and depression as comorbidities among these patients.Material and Method: The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Another study done by Sharma 17 , in patients with Tension Type headache, majority (32.5%) have passed matriculation exam, followed by those in intermediate level. Also study done by Kafle et al 18 showed 34.7% of the people with secondary level education status which was the maimum number followed by primary school level (23.3%).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Another study done by Sharma 17 , in patients with Tension Type headache, majority (32.5%) have passed matriculation exam, followed by those in intermediate level. Also study done by Kafle et al 18 showed 34.7% of the people with secondary level education status which was the maimum number followed by primary school level (23.3%).…”
Section: Discussionmentioning
confidence: 90%
“…Studies done in TUTH by Sharma 17 showed 62.5% females and study done by Khalid et al 23 showed 61.92% female predominance. Study done by Kafle et al 18 showed 78.7% of the sufferers were female.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations